Pengembangan Fitur Manajemen Uang Kuliah Tunggal (UKT) Mahasiswa pada Sistem Registrasi Universitas Jambi - Sigit Indrawijaya; Reni Aryani; Dawam Suprayogi (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The University of Jambi (UNJA) currently manages the Single Tuition Fee (UKT) manually using Microsoft Excel, which causes various problems such as the length of the UKT determination process, data duplication, and difficulty in accessing the UKT determination history by the leadership.This research aims to develop UKT management features on the UNJA registration system to increase the effectiveness and automation of the UKT management process. System development is carried out using the Star Life Cycle Model method by implementing the features of the student UKT program proposal and uploading the required files. The research produced a prototype of a web-based registration system with a UKT Management feature that allows the process of determining and submitting a reduction / exemption of UKT to be carried out systematically. The implementation of this system is expected to overcome problems in managing UKT at UNJA such as duplication of UKT reduction which is detrimental to the institution in terms of finance.